Magnetic resonance imaging (Eurasian Journal of Research, Development and Innovation, 2024)
MRI machine is a method that uses a magnetic field in addition to radio waves to create detailed images of the various tissues and organs of the body that are to be examined. Some MRI devices consist of a large magnet in the form of a tube. When the patient lies inside the device, the magnetic field works to reorganize the hydrogen atoms in the patient’s body. Radio waves emit weak signals, and through it, cross-sectional images are produced, and three-dimensional images can also be issued. In addition to the existence of a type of magnetic resonance imaging known as functional magnetic resonance imaging, this type is used to clarify the anatomy of the brain and also demonstrates metabolic changes in the brain. In addition, it helps in diagnosing damage associated with brain injuries and also diagnosing Alzheimer's disease